Nutraceutical management of male infertility-towards new generation therapeutics - Ekerin, Olabode; K., Calistus Okechukwu (Journal of Ideas in Health, 2021)
Infertility is one of the most significant public health-related concerns globally. Both male and female factors can cause it. Male factors include poor sperm quality, idiopathic oligospermia, asthenozoospermia, and isolated asthenozoospermia. Many substances, collectively known as nutraceuticals, have been studied for their capacity to enhance hormonal state and sperm parameters through different mechanisms. Nutraceuticals are components in dietary supplements prescribed to prevent or treat a wide range of diseases. This article aims to highlight certain nutrients that can help improve male fertility based on recent advancements in the management of male infertility.